Impact of anterior commissure invasion on the oncological efficacy of transoral laser microsurgery for T1 glottic cancer - Wang, Qi; Huang, YangYiYi; Li, Yun; Ling, Yi; Zhou, JianSheng; Lou, ZheWei; Fan, Guo-Kang (Frontiers in Oncology, 2025)
BackgroundIn glottic laryngeal cancer, anterior commissure (AC) involvement affects prognosis. T staging ignores AC subregion involvement and TNM staging may not suit as an AC prognostic indicator. We explored how AC involvement degree impacts prognosis in T1 glottic laryngeal cancer treated with transoral laser microsurgery (TLM). Methods: A retrospective study included 367 T1 glottic cancer patients undergoing TLM in the Department of Otorhinolaryngology at the Second Affiliated Hospital of Zhejiang University School of Medicine from January 2012 to June 2024. There were 348 males and 19 females, aged 42 – 87 years (average 63.7, SD 8.9). The median follow-up was 49.5 months (6.2 - 190.7). Staging was performed according to the degree of AC involvement (AC0–AC3) as suggested by Rucci L, and we analyzed its impact on prognosis.ResultsNo major complications occurred. Twenty-five patients had recurrence (6 open surgery, 17 repeat TLM, 2 palliative treatment); 4 died. The 5-year local control rate for T1 was 91.5%, and the disease-related survival rate was 98.3%. Specifically, for T1a, they were 92.3% and 99.0% respectively, and for T1b, they were 87.5% and 97.6% respectively. Patients with severe AC involvement (AC3) significantly affected the local control rate (p = 0.014), and the 5-year local control rate for AC3 was 61.0%. Intraoperative margin pathological examination had an impact on the local control rate and the disease-related survival rate (the p values of the log-rank test were 0.011 and 0.045 respectively). Poorly differentiated pathological results had an impact on the disease-related survival rate (the p value of the log-rank test was 0.001). Univariate analysis of the Cox proportional hazards regression model showed that margin pathological examination and AC3 were important negative prognostic factors for the local control rate.ConclusionTLM shows good oncological efficacy in the treatment of T1 glottic cancer. Our study provides evidence that it is not the T stage but the severe involvement of the AC that affects the prognosis of T1a and T1b. For patients with severe AC involvement, TLM should be chosen cautiously, and open partial laryngectomy may serve as an alternative option.